Implementing Prehospital Evidence-Based Guidelines: A Systematic Literature Review. (4th July 2018) - Fishe, Jennifer N.; Crowe, Remle P.; Cash, Rebecca E.; Nudell, Nikiah G.; Martin-Gill, Christian; Richards, Christopher T.
Abstract: Objective : As prehospital research advances, more evidence-based guidelines (EBGs) are implemented into emergency medical services (EMS) practice. However, incomplete or suboptimal prehospital EBG implementation may hinder improvement in patient outcomes. To inform future efforts, this study's objective was to review existing evidence pertaining to prehospital EBG implementation methods.Methods : This study was a systematic literature review and evaluation following the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology. PubMed, EMBASE, Scopus, and Google Advanced Search were searched without language or publication date filters for articles addressing prehospital EBG implementation. Conference proceedings, textbooks, and non-English articles were excluded. GRADE was applied to the remaining articles independently by three of five study investigators. Study characteristics and salient findings from the included articles are reported.Results : The systematic literature review identified 1, 367 articles, with 41 meeting inclusion criteria. Most articles described prehospital EBG implementation ( n = 24, 59%), or implementation barriers ( n = 13, 32%). Common study designs were statement documents ( n = 12, 29%), retrospective cohort studies ( n = 12, 29%), and cross-sectional studies ( n = 9, 22%). Using GRADE, evidence quality was rated low ( n = 18, 44%), or very low ( n = 23, 56%). Salient findings from the articles included: (i) EBG adherence and patient outcomes depend upon successful implementation, (ii) published studies generally lack detailed implementation methods, (iii) EBG implementation takes longer than planned (mostly for EMS education), (iv) EMS systems' heterogeneity affects EBG implementation, and (v) multiple barriers limit successful implementation (e.g., financial constraints, equipment purchasing, coordination with hospitals, and regulatory agencies). This review found no direct evidence for best prehospital EBG implementation practices. There were no studies comparing implementation methods or implementation in different prehospital settings (e.g., urban vs. rural, advanced vs. basic life support).Conclusions : While prehospital EBG implementation barriers are well described, there is a paucity of evidence for optimal implementation methods. For scientific advances to reach prehospital patients, EBG development efforts must translate into EMS practice. Future research should consider comparing implementation methodologies in different prehospital settings, with a goal of defining detailed, reproducible best practices.